The Effect of Problem Based Learning Model Assisted by Quizizz Media and Reading Interest on Mastery of Fact and Opinion Sentences on News Texts - Widyastuti, Indri; Afnita, Afnita (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
The purpose of this study are as follows. First, to describe the influence of the Problem Based Learning learning model assisted by Quizizz media on the mastery of factual and opinion sentences in news texts. Second, to describe the influence of the Problem Based Learning learning model assisted by Quizizz media on the mastery of factual and opinion sentences for students with high reading interest. Third, to describe the influence of the Problem Based Learning learning model assisted by Quizizz media on the mastery of factual and opinion sentences for students with low reading interest. Fourth, to explain the interaction between the Problem Based Learning learning model assisted by Quizizz media and reading interest on the mastery of factual and opinion sentences in news texts. This type of research is quantitative research with an experimental method. The population of this study were students of class VII of UPTD SMP Negeri 1, Harau District who were registered in the 2024/2025 academic year. The sample in this study was class VII.F as the experimental class and class VII.E as the control class. The instruments used in this study were a reading interest questionnaire and an objective test of factual and opinion sentences in news texts. The data collection technique in this study was that students in the control class and experimental class answered questions in the reading interest questionnaire. Furthermore, students answered questions on the objective test of factual and opinion sentences in news texts. The data analysis process was carried out by utilizing the IMB SPSS Statistics 25 application. Based on the results of the analysis and discussion in this study, several conclusions can be drawn. First, there is an influence of the use of the Problem Based Learning learning model assisted by the Quizizz media on the mastery of factual and opinion sentences in news texts of class VII students of UPTD SMP Negeri 1, Harau District with a sig value (0.001) smaller than 0.05. Second, there is an influence of the use of the Problem Based Learning learning model assisted by the Quizizz media on the mastery of factual and opinion sentences in news texts of class VII students of UPTD SMP Negeri 1, Harau District who have high reading interest with a sig value (0.001) smaller than 0.05. Third, there is an influence of the use of the Problem Based Learning learning model assisted by the Quizizz media on the mastery of factual and opinion sentences in news texts of class VII students of UPTD SMP Negeri 1, Harau District who have low reading interest with a sig value (0.046) smaller than 0.05. Fourth, there is no interaction between the Problem Based Learning learning model assisted by Quizizz media and reading interest in influencing the mastery of factual and opinion sentences in news texts of class VII students at UPTD SMP Negeri 1, Harau District.